Blended learning approach improves teaching in a problem-based learning environment in orthopedics - a pilot study - Back, David A.; Haberstroh, Nicole; Antolic, Andrea; Sostmann, Kai; Schmidmaier, Gerhard; Hoff, Eike (BMC medical education, 2014)
While e-learning is enjoying increasing popularity as adjunct in modern teaching, studies on this topic should shift from mere evaluation of students’ satisfaction towards assessing its benefits on enhancement of knowledge and skills. This pilot study aimed to detect the teaching effects of a blended learning program on students of orthopedics and traumatology in the context of a problem-based learning environment.
Gesehen am 16.10.2020